The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1155/2012/413583
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Modal Analysis of Gasketed and Nongasketed Bolted Flanged Pipe Joints: FEA Approach

Abstract: It is widely known that resonance can quickly lead to failure in vibrating bolted flanged pipe joints. Condition monitoring is performed time to time in some industries for smooth operation of a system, whereas mostly trial-and-error tests are performed to control vibration. During all this process, the inherent design problems are not considered. A bolted flange joint in piping system is not a simple problem, being the combination of flange, gasket, bolts, and washers. The success of a bolted flanged pipe joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…In a gasketed joint, the presence of the gasket and rotation of flanges results in joint relaxation and improper preloading of the bolts. In addition to this, gasket crushing and flange yielding limits higher pre-load [1,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Bolt quality and proper tooling has been proven to be important factors in getting proper pre-load in the joint [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a gasketed joint, the presence of the gasket and rotation of flanges results in joint relaxation and improper preloading of the bolts. In addition to this, gasket crushing and flange yielding limits higher pre-load [1,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Bolt quality and proper tooling has been proven to be important factors in getting proper pre-load in the joint [1].…”
Section: Introductionmentioning
confidence: 99%
“…Gasketed flanged pipe joints are considered prone to failure, in terms of strength and sealing capability, during bolt up and operating conditions of even internal pressure loading only. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Their performance can be worse under combined loading applications. 1,[3][4][5][6]8,[10][11][12][13][14][15][16][17] However, it is also reported that a gasketed joint can perform well provided the joint assembly is made properly and with great care, which may be possible in a controlled laboratory environment but cannot be ensured in the field applications.…”
Section: Introduction and Experimental Setupmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Their performance can be worse under combined loading applications. 1,[3][4][5][6]8,[10][11][12][13][14][15][16][17] However, it is also reported that a gasketed joint can perform well provided the joint assembly is made properly and with great care, which may be possible in a controlled laboratory environment but cannot be ensured in the field applications. 1,[3][4][5]11,[13][14][15]17 Although certain numerically studies were performed under combined pressure and different (static and transient) thermal loadings up to 400 • C, 6,8,12,16,[20][21][22]…”
Section: Introduction and Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Os autores concluíram que a configuração na forma de U da o melhor desempenho com taxa de vazamento não mensurável sob carga aplicada representada em termos de tensão global de 0,67 Mpa. Foi feita análise de tensão usando o método de elementos finitos com a ferramenta ABAQUS®, e se conclui que o projeto da ranhura em U tem o melhor desempenho de vedação Abid et al (2012). apresentam resultados detalhados de análise modal por elementos finitos 3D e análise modal matemática para determinar as frequências naturais e modos de vibrar de junções flangeadas, para junta de vedação, com e sem rebaixo na face; fazendo a comparação com junção flangeada sem junta de vedação.…”
unclassified